Posouzení investičního záměru autorizace nové značky pro společnost MOTORTEC spol. s r.o. - Kubját, Jiří (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Diplomová práce se zabývá posouzením investičního záměru pro společnost XYZ spol. s r. o. Společnost XYZ působí na poli autorizovaných dealerů automobilů ___, ___, ___ a ___. Jedná se o investici do autorizace nové značky a investici do budovy, která bude sloužit jako showroom a servis. Společnost postaví budovu ve vlastní režii. Cílem diplomové práce je vyhodnocení autorizace 6 možných vybraných značek. Mezi vybrané značky patří A, B, C, D, E a F.

This thesis deal with the judgement of investment intention for the company XYZ Ltd. The company XYZ operates as a authorized cars dealer for ___, ___, ___ and ___. The investment is planned for acquiring the sale authorization for a new brand and for the construction of a new building, which would include showroom and service spaces. The company plans on constructing the building on its own. The goal of the thesis is to evaluate possibilities for gaining authorization for one of six selected brands. The selected brands include A, B, C, D, E and F.
Judgement of Investment Intention of New Brand Name authorization For Company MOTORTEC Ltd.
Keywords: Autorizace; investiční záměr; investice; efektivnost investice; analýza rizik; čistá současná hodnota; vnitřní výnosové procento; index ziskovosti.; Authorization; investment project; investments; investment efficiency; risk analysis; net present value; internal rate of return; profitability index.